Co-constructing an essay: collaborative writing in class and on wiki - Ansarimoghaddam, Shokoufeh; Tan, Bee Hoon (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper compares the quality of students’ individually written essays resulting from both collaborative writing through wiki and face-to-face collaborative writing. Face-to-face collaborative writing refers to in class meeting of students for writing essays collaboratively. The study employed a counterbalance research design. Participants of the study were thirty tertiary ESL students from one class. They were divided into two experiment groups with each comprising 15 students. Before the experiment, each participant wrote an essay. After that they were given two treatments of collaborative writing through wiki and face-to-face. The order of giving the two treatments was different for the two groups to eliminate any practice effect. After an introduction to the collaborative process, the participants wrote two argumentative essays in groups, and wrote two essays individually. After the experiment, a semi-structured interview was conducted as a triangulation measure. Results suggest that collaborative writing using the wiki software can be more effective, and more enjoyable, than collaboration resulting from face-to-face meeting.